BANGKITAN PERJALANAN PADA PERUMAHAN BOUGENVLLE DI PALEMBANG - Hamdi Hamdi (Politeknik Negeri Sriwijaya, 2011)
Transportation problems arise as an impact when the interaction among the system of land-use, transportation network and demand of mobility has no longer appropriate. The development of new residential housing complexes including other infrastructures facilities energize the change in land use, which is in turn affecting the transportation network and mobility. This research is aimed to model a trip generation produced by Bougenville housing complex. These informations then could be used as a guideline to make decision of infrastructure management in order to minimize transportation problems from this zone. Multiple regression (MR) analysis was used to develope a Bougenville’s trip production mode. The analyses proved that the parameter of family size (X1), motor-cycle ownership and household income (X4) played significance role on the model whilst car-ownership (X2) was otherwise. The combination of X1, X3 and X4 by using an MR analysis come up with R2 of 0.711. Hence, this model is chosen as trip production model to predict trip production of Bougenville residential housing.